The effects of two true-ileal-digestible lysine concentrations, Optipak®, ractopamine hcl (paylean®), and their combinations, on the growth performance and carcass characteristics of finishing pigs reared in commercial facility - Bergstrom, J.R.; Nelssen, Jim L.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,207 pigs (PIC, 337 × 1050) were used in a 28-d experiment in a commercial research barn to evaluate the effects of two true ileal digestible (TID) lysine concentrations, Optipak®, ractopamine HCl, and their combinations, on the growth performance and carcass characteristics of finishing pigs. There were 6 replicates per treatment (with the exception of one treatment that had 5), and 19 to 26 pigs per pen. Pigs were weighed at approximately 220 lb and allotted to six, corn-soybean meal-based dietary treatments. Four diets were formulated to 0.80% TID lysine: a control diet, the control diet with 5 lb/ton of Optipak®, the control diet with 4.5 g/ton of ractopamine HCl, or the control diet with both Optipak® and ractopamine HCl. The two remaining diets were formulated to 0.94% TID lysine and contained 4.5 g/ton of ractopamine HCl, with or without 5 lb/ton of Optipak®. The treatment structure provided for two 2 × 2 factorial arrangements of treatments. The first factorial utilized the four 0.80% TID lysine diets to evaluate the effects of Optipak® and ractopamine HCl. The second factorial utilized the four diets containing ractopamine HCl to evaluate the effects of TID lysine and Optipak®. Pigs fed diets containing ractopamine HCl had improved (P<0.04) ADG, F/G, and final weight. In the diets containing ractopamine HCl, ADFI tended (P<0.07) to be lower for pigs fed 0.94% TID lysine. There were no other differences in growth performance among the treatments. For carcass characteristics, plant live weight, hot carcass weight, and dressing percentage were improved (P<0.04) for pigs fed ractopamine HCl. Additionally, loin depth increased (P<0.03) when Optipak® was included in the diet. This experiment provides further evidence that ractopamine HCl improves late-finishing growth performance, hot carcass weight, and dressing percentage. Although Optipak® did not improve growth performance, it increased loin depth. The different responses to ractopamine HCl and Optipak® suggest that the incentives for justifying their use need to be evaluated independently.
Keywords: Swine; Amino acids; Feed ingredient; Lysine; ractopamine HCl